University-schools collaboration through the teaching practicum - Frodden, Cristina; Lopez, Angela (Íkala, Revista de Lenguaje y Cultura, 1998)
This article adresses the authors experience carrying out their teaching practice of english in a group of public schools in Medellin. This teaching practice which is part of an undergraduate language teaching program, is based on principles of collaborative action research. It seeks to enhance the quality of basic education. Since all participants have the chance to develop knowledge, discuss new ideas and feed curricular changes, the practicum is a fruitful learning context.